1996
DOI: 10.1123/ssj.13.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Networks: Producing Olympic Ice Hockey for a National Television Audience

Abstract: This paper presents an ethnographic study of the Canadian Television Network’s (CTV) production of the 1988 Winter Olympic ice-hockey tournament. Interview data and media documents are analyzed to uncover how CTV strategically employed hockey as a spectacle of accumulation to boost ratings, expand market positioning, and to attract sponsors while blocking media competitors. At another level of understanding, ethnographic observations of the televisual labor process provide insights into how Olympic broadcastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 0 publications
1
38
0
Order By: Relevance
“…Transnational media conglomerates like Rupert Murdock's News Corporation mobilize popular understandings and particular (local) national identifications around sport in the United States, the United Kingdom, and Australia to enhance profits and fashion "a global media entertainment empire" (Andrews, 2003, p. 235) As an oligarchy, media structures enjoy the upper hand in encoding sporting texts. Television producers of such worldwide media events as the Olympic Games attempt to create spectacles of accumulation and legitimation in an effort to enhance profits and separate their programming from their competitors' (MacNeill, 1996). In doing so sport media producers tend to avoid controversial framings, thus closing "the range of possible meanings" to which a diverse array of viewers must always respond, although these are always contested and not univocal (Jhally, 1989, p. 89).…”
Section: Rearticulating Power: Critical Theorists Respond To Economicmentioning
confidence: 96%
“…Transnational media conglomerates like Rupert Murdock's News Corporation mobilize popular understandings and particular (local) national identifications around sport in the United States, the United Kingdom, and Australia to enhance profits and fashion "a global media entertainment empire" (Andrews, 2003, p. 235) As an oligarchy, media structures enjoy the upper hand in encoding sporting texts. Television producers of such worldwide media events as the Olympic Games attempt to create spectacles of accumulation and legitimation in an effort to enhance profits and separate their programming from their competitors' (MacNeill, 1996). In doing so sport media producers tend to avoid controversial framings, thus closing "the range of possible meanings" to which a diverse array of viewers must always respond, although these are always contested and not univocal (Jhally, 1989, p. 89).…”
Section: Rearticulating Power: Critical Theorists Respond To Economicmentioning
confidence: 96%
“…Further, such large-scale sporting events are often the site for study due to the large media audiences generated by television broadcasters producing telecasts focused on their 'home' viewers in order to increase the interest and participation of viewers in a particular nation (cf., Billings, 2010a, 2010b;Billings, 2009;Billings and Eastman, 2003;Eastman and Billings, 1999;Larson and Rivenburgh, 1991;MacNeill, 1996;Silk and Falcous, 2005). In interviews with the American broadcaster of the Olympic Games, Billings (2008) found that US National Broadcasting Corporation (NBC) executives attempted to create a broadcast that featured athletes of many nations, while maintaining an Ameri-centric focus to ensure that US viewers continued to watch the Olympics coverage through featuring US home athletes more often than foreign athletes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…5 By contrast, M. Macneil's critical observations of the 1988 Calgary Winter Olympic games productions by the Canadian Television (CTV) network did not cede anywhere near as much autonomy to the production crew. 6 She suggested that there was a degree of human agency at the production site, but qualified this statement with the 2 CULTURE, SPORT, SOCIETY recognition that the production process was highly conventionalized, following historical and cultural televisual codes of practice. Gruneau similarly concluded that the practices used in the Canadian Broadcasting Corporation's coverage of World Cup Skiing comprised a set of unconscious and informal rules and conventions picked up 'on the job'.…”
mentioning
confidence: 97%